Influência de recursos energéticos distribuídos na qualidade da energia elétrica - Gimenes, Thayana Knupp (2020)
The continuous increase in the demand for electric energy increases the interest and participation of distributed generation in the global energy matrix. Worldwide, the most common distributed generation is the generation of photovoltaic solar energy, which is considered a clean energy source. This generation technology depends on climatic conditions, therefore its generation is intermittent, which causes a variation in power in the distribution system. Energy storage systems are used to mitigate intermittency problems. There are several types of storage, but the most used to minimize the power variation in residential distributed systems is the battery. As the use of distributed photovoltaic generation is the fastest growing in the world, an increase in the use of batteries is also expected. These two devices change the power flow configuration of the distribution system and make use of power electronics. In this way, the concern with the quality of electric power is increased due to the electromagnetic disturbances that this equipment can insert, the main ones being voltage variation and imbalance, voltage and frequency fluctuation, and harmonic distortion. Therefore, the present research aimed to analyze the impact on the quality of electrical energy of distributed systems considering the variation of the system load, the variation of penetration, and the allocation of distributed generation and batteries, represented by the output of the inverters. For this, the IEEE 34 bus system was used, adapted to the Brazilian electrical system, and considering low voltage branches. The system was implemented and simulated in ATPDraw® in conjunction with Matlab® and voltage variation and imbalance and harmonic distortion for primary and secondary distribution systems were analyzed, as well as load variation analysis. The results obtained showed that for each electromagnetic disturbance there is an allocation that results in smaller insertions of this disturbance, and it is not possible to have an allocation, among those analyzed, that help to mitigate all disturbances in the system. The penetration of distributed generation directly affects the disturbances inserted, causing the harmonics to increase. As for the long-term voltage variation and voltage imbalance, it depends on the system configuration. It was possible to reach the conclusion that to determine mainly the way in which distributed generation and batteries will be allocated, it is necessary to study the electrical system in question.